Broadband Nonlinear Optical Response of Nitrogen-Doped Diamond - Xiao, Zhengguo; Fang, Yu; Song, Yinglin; She, Yanchao; Tian, Changhai; Zhang, Jie; Cui, Liqin; Li, Yong (Frontiers in Materials, 2021)
A nitrogen-doped diamond crystal with (111) orientation was synthesized with an NaN3 additive in the FeNi-C system at a pressure of 6.5 GPa and a temperature of 1,310°C, using the temperature gradient growth (TGG) method. Spectroscopic properties such as the absorption spectrum and the Raman spectrum as well as the Fourier transform infrared (FTIR) spectrum were studied. FTIR spectroscopy of the C-N vibrational modes at 1,344 and 1,130 cm−1 suggested a nitrogen content of 310 ppm. Its nonlinear optical (NLO) response was investigated using the Z-scan technique under the femtosecond regime. Due to the presence of nitrogen defects, the synthesized crystal performed large nonlinear absorption under both 800- and 532-nm wavelength excitations. However, intrinsic diamond only experiences nonlinear refraction under these two wavelength excitations. Its broadband NLO properties indicated that nitrogen-doped diamond crystals were suitable for the application of ultrafast optical devices.